(3edGc GdJChjd GdbGWY dPhi GdGdMGO hGdJYWjd aj JhLjg GdeJTGHg ef Bi GdJfRjds - (3CMeO Hf EHQGgje Hf GdRHjQ GdKbaj GdZQfGWj, CHh LYaQ,J (B708 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeGfM ef TGA eG TGA hGdZGaQ Ohf GdTQc s
(3BNQgG (B:s
(3ef JChjd ShQI (B" (3bd CYhP HQH Gdadb (B" (3CYfi Cf jchf ai GdCZdH GdcKjQ eSGhjkG ddChd Ch CYQa adgPG LGO eVGakG Edi GdXGgQ efgGhGdgd CYde s
(3ai CKfGA JChjd ShQI GdGfTbGb HjGVs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B86s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs